Experimental study on failure characteristics of single-sided unloading rock under different intermediate principal stress conditions - Liu, Chongyan; Zhao, Guangming; Xu, Wensong; Meng, Xiangrui; Liu, Zhixi; Cheng, Xiang; Lin, Gang (International journal of mining science and technology, 2023)
Investigation of unloading rock failure under different σ2 facilitates the control mechanism of excavation surrounding rock. This study focused on single-sided unloading tests of granite specimens under true triaxial conditions. The strength and failure characteristics were studied with micro-camera and acoustic emission (AE) monitoring. Furthermore, the choice of test path and the effect of σ2 on fracture of unloading rock were discussed. Results show that the increased σ2 can strengthen the stability of single-sided unloading rock. After unloading, the rock's free surface underwent five phases, namely, inoculation, particle ejection, buckling rupture, stable failure, and unstable rockburst phases. Moreover, at σ2≤30 MPa, the b value shows the following variation tendency: rising, dropping, significant fluctuation, and dropping, with dispersed damages signal. At σ2≥40 MPa, the tendency shows: a rise, a decrease, a slight fluctuation, and final drop, with concentrated damages signal. After unloading, AE energy is mainly concentrated in the micro-energy range. With the increased σ2, the micro-energy ratio rises. In contrast, low, medium and large energy ratios drop gradually. The increased tensile fractures and decreased shear fractures indicate that the failure mode of the unloading rock gradually changes from tensile-shear mode to tensile-split one. The fractional dimension of the rock fragments first increases and then decreases with an inflection point at 20 MPa. The distribution of SIF on the planes changes as σ2 increases, resulting in strengthening and then weakening of the rock bearing capacity.